HP : imprinting the global health sector - Jones, Jamie; Augustine, Grace ([London] : SAGE, 2016)
Hewlett-Packard (HP) had a long history of engaging in corporate citizenship, dating back to its founding. By 2009, however, under the leadership of CEO Mark Hurd, the company had lost its focus on corporate social responsibility (CSR). The HP board, however, did not want to let CSR go by the wayside; in fact, it wanted HP to reorganize and restrategize its approach to corporate citizenship. This case focuses on this strategic transformation from traditional, cost-centre CSR to business-aligned social innovation.
Originally Published in: Jones, J., & Augustine, G. (2015). HP: Imprinting the Global Health Sector. 5-314-501. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Hewlett-Packard Company; Social responsibility of business -- Case studies; Public health administration -- Case studies